Identification of urban waste based on environmentally friendly products in biology education - Silfia Ilma; Fitri Wijarini (Biosfer: Jurnal Pendidikan Biologi, 2026)
Environmental issues are a major concern worldwide. Improperly managed waste is one of the causes of environmental damage. Household waste is the largest contributor to waste in Indonesia. Household waste consists of food scraps, plastic, cans, bottles, and other liquid waste. This study aims to identify the types of materials that can be used as recycled products in biology education especially environmental education learning, processing methods, and suitability with learning plans. The method in this research is systematic literature review (SLR). Reference searches used the Publish or Perish 8 application by analyzing articles indexed by Google Scholar. After conducting the identification, screening, eligibility, and inclusion processes, 10 articles were obtained from Google Scholar. All articles were explained for their suitability with the content of the material in the Environmental Education lesson plan. The findings in this study indicate that materials that can be processed into environmentally friendly products are plastic packaging, plastic bottles, diapers, and used cooking oil. This waste processing can be done using easily available additional materials and simple tools. This study provides a reference for household waste management, contributes to reducing the volume of waste ending up in landfills, supports environmental conservation by encouraging the utilization of waste that is still useful, and increases awareness and implementation of sustainable waste management practices in the community.